The relationship between religious attitudes and attachment in late adolescence - Kantar, Dejan (Psihološka istraživanja, 2020)
The purpose of this study, based on the findings that there is a link between the attachment system and the different aspects of religiosity, is to examine the degree of expression of four religious attitudes – literal belief, post-critical belief, relativism, and external critique, as well as their potential relationships with different qualities of parental attachment in late adolescence. The sample is represented by 301 respondents – 176 girls and 125 boys, average age 19.2 years, who completed the Post-Critical Belief Scale and the modified version of the Experiences in Close Relationships Inventory. The results indicate that adolescents have the highest tendency towards post-critical belief and the least tendency towards external criticism, where girls are on average more likely to have a literal and post-critical belief, while boys are more inclined to relativism and external critique. Furthermore, the results showed that among adolescents expressing different types of attachment there are significant differences in leaning towards literal and post-critical belief, external critique, but not relativism, i.e. it was found that higher anxiety and lower avoidance predict a greater tendency towards literal and post-critical belief, whereas a higher avoidance predict a stronger tendency towards external critique, but with the low percentage of explained variance. The results were interpreted based on the context of the findings of previous researches and were perceived in the light of current models that explain the relationship between the quality of attachment and religion.